Methylphenidate and sleep difficulties in children and adolescents with ADHD: results from the 2-year naturalistic pharmacovigilance ADDUCE study - Häge, Alexander; Man, Kenneth K. C.; Inglis, Sarah K.; Buitelaar, Jan; Carucci, Sara; Danckaerts, Marina; Dittmann, Ralf; Falissard, Bruno; Garas, Peter; Hollis, Chris; Konrad, Kerstin; Kovshoff, Hanna; et al. (Journal of attention disorders, 2024)
OBJECTIVE: Short-term RCTs have demonstrated that MPH-treatment significantly reduces ADHD-symptoms, but is also associated with adverse events, including sleep problems. However, data on long-term effects of MPH on sleep remain limited. - METHODS: We performed a 2-year naturalistic prospective pharmacovigilance multicentre study. Participants were recruited into three groups: ADHD patients intending to start MPH-treatment (MPH-group), those not intending to use ADHD-medication (no-MPH-group), and a non-ADHD control-group. Sleep problems were assessed with the Children's-Sleep-Habits-Questionnaire (CSHQ). - RESULTS: 1,410 participants were enrolled. Baseline mean CSHQ-total-sleep-scores could be considered clinically significant for the MPH-group and the no-MPH-group, but not for controls. The only group to show a significant increase in any aspect of sleep from baseline to 24-months was the control-group. Comparing the MPH- to the no-MPH-group no differences in total-sleep-score changes were found. - CONCLUSION: Our findings support that sleep-problems are common in ADHD, but don't suggest significant negative long-term effects of MPH on sleep.
Gesehen am 05.11.2024